Catching stories : a practical guide to oral history - DeBlasio, Donna Marie (Swallow Press, 2009)
Why do oral history? / Howard L. Sacks -- Planning an oral history project / Stephen H. Paschen -- Ethics and politics in oral history research / Howard L. Sacks -- Legal issues / David H. Mould -- Interviewing / David H. Mould -- Transcribing oral history / Donna M. Deblasio -- Catching sound and light / Charles F. Ganzert -- Audio and video recording / David H. Mould and Charles F. Ganzert -- Archiving oral history / Stephen H. Paschen -- Funding / Donna M. Deblasio and David H. Mould -- Sharing oral history / Donna M. Deblasio